DEVELOPMENT OF GROSS MOTOR SKILLS SCREENING TOOL FOR INCLUSIVE EDUCATION (Proceedings of International Conference on Special Education, 2015)
Inclusive education is a strategy to increase the rate of participation of school-aged children with special needs. To ensure their active integration, an assessment of their strengths and weaknesses must be established, particularly in their gross motor skills (GMS). The purpose of this study is to develop a GMS screening tool that would help teachers in special education classes to identify the needs of children with disabilities. This study is part of a bigger qualitative descriptive psychometric study on developing a tool to measure and evaluate functional skills of children aged 4 to 6 years. The tool was drafted based on developmental milestones of typically developing children. It was subjected to face, content, and context validation by a panel of experts composed of physical therapists who had at least 2 years experience in handling pediatric patients. It was revised according to the recommendations of the expert panel and was resend for the second time to them for final approval. The tool was preliminarily introduced and utilized by elementary teachers in one urban elementary school and in one rural elementary school. It was conducted with consent among regular and special education students. Based on the pilot testing, the tool needs to be revised through construct validation in order for it to be sensitive in showing the difference in the scores of typically developing children compared to the scores of children with special needs; further training of the teacher assessors must be done to improve inter-tester and intra- tester reliability.